Neurological manifestations and neuro‐invasive mechanisms of the severe acute respiratory syndrome coronavirus type 2. (16th June 2020) - Vonck, K.; Garrez, I.; De Herdt, V.; Hemelsoet, D.; Laureys, G.; Raedt, R.; Boon, P.
Abstract : Background and purpose: Infections with coronaviruses are not always confined to the respiratory tract and various neurological manifestations have been reported. The aim of this study was to perform a review to describe neurological manifestations in patients with COVID‐19 and possible neuro‐invasive mechanisms of Sars‐CoV‐2. Methods: PubMed, Web of Science and COVID‐dedicated databases were searched for the combination of COVID‐19 terminology and neurology terminology up to 10 May 2020. Social media channels were followed up between 15 March and 10 May 2020 for postings with the same scope. Neurological manifestations were extracted from the identified papers and combined to provide a useful summary for the neurologist in clinical practice. Results: Neurological manifestations potentially related to COVID‐19 have been reported in large studies, case series and case reports and include acute cerebrovascular diseases, impaired consciousness, cranial nerve manifestations and autoimmune disorders such as the Guillain–Barré syndrome often present in patients with more severe COVID‐19. Cranial nerve symptoms such as olfactory and gustatory dysfunctions are highly prevalent in patients with mild to moderate COVID‐19 even without associated nasal symptoms and often present in an early stage of the disease. Conclusion: Physicians should be aware of the neurological manifestations in patients with COVID‐19, especially when rapid clinical deterioration occurs. The neurological symptoms in COVID‐19 patients may be due to direct viral neurological injury or indirect neuroinflammatory and autoimmune mechanisms. No antiviral treatments against the virus or vaccines for its prevention are available and the long‐term consequences of the infection on human health remain uncertain especially with regard to the neurological system.